2016
DOI: 10.1038/srep30203
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analyses of the bZIP family reveal their involvement in the development, ripening and abiotic stress response in banana

Abstract: The leucine zipper (bZIP) transcription factors play important roles in multiple biological processes. However, less information is available regarding the bZIP family in the important fruit crop banana. In this study, 121 bZIP transcription factor genes were identified in the banana genome. Phylogenetic analysis showed that MabZIPs were classified into 11 subfamilies. The majority of MabZIP genes in the same subfamily shared similar gene structures and conserved motifs. The comprehensive transcriptome analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 55 publications
8
49
0
Order By: Relevance
“…In summary, the different gene family members exhibited great disparities under different dehydration and rehydration stresses. This phenomenon also exists in many higher plants (Wang et al, 2014;Hu et al, 2016). In addition, many cis-acting regulatory elements were identified in response to drought stress, clearly indicating that the PyMAPKKK gene family is involved in dehydration and rehydration, not only at a transcript level but also at a regulatory level.…”
Section: Expression Analysis Of Pymapkkk Genes When Exposed To Differmentioning
confidence: 78%
“…In summary, the different gene family members exhibited great disparities under different dehydration and rehydration stresses. This phenomenon also exists in many higher plants (Wang et al, 2014;Hu et al, 2016). In addition, many cis-acting regulatory elements were identified in response to drought stress, clearly indicating that the PyMAPKKK gene family is involved in dehydration and rehydration, not only at a transcript level but also at a regulatory level.…”
Section: Expression Analysis Of Pymapkkk Genes When Exposed To Differmentioning
confidence: 78%
“…Post-genomic research has strongly indicated role of the bZIP transcription factors in fruit development process in many crops (Levi et al, 2006; Costa and Alba, 2010; Rohrmann et al, 2011). Recently, extensive involvement of bZIPs and WRKY in fruit development and post-harvest ripening has been demonstrated (Goel et al, 2016; Hu et al, 2016a) by comparing its expression pattern at different stages of banana development. The high expression levels of MabZIPs in fruit developmental and ripening is postulated to control the fruit quality of banana.…”
Section: Banana Ripeningmentioning
confidence: 99%
“…Commensurate increase in transcription levels was also observed in other plants such as cassava (Hu et al, 2016b), Brachypodium distachyon (Liu and Chu, 2015) and maize (Wei et al, 2012). Post-genomic discovery of bZIPs (Hu et al, 2016a), microRNAs (Chai et al, 2015) along with key metabolites (Pandey et al, 2016) is expected to expedite the molecular breeding process by ushering in, understanding the role, these transcription factors in signal transduction, developmental processes and responses to abiotic stress in banana.…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%
“…Meanwhile as a large annual monocotyledonous herbaceous plant, banana production is frequently destroyed by various abiotic stresses during growth and development, such as cold, salt and drought [26][27][28] . Thus, investigations of key candidate genes involved in fruit development and responses to multiple stresses, based on complete genome sequences, are necessary to improve quality and enhance stresses tolerance [29,30] . However, few studies on identification and characterization of banana genes based on genome sequencing data have been reported [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigations of key candidate genes involved in fruit development and responses to multiple stresses, based on complete genome sequences, are necessary to improve quality and enhance stresses tolerance [29,30] . However, few studies on identification and characterization of banana genes based on genome sequencing data have been reported [30] . To our knowledge, only one BAM gene has been reported to have been cloned in banana [31] .…”
Section: Introductionmentioning
confidence: 99%